Saturday

December 20, 2014

December 20, 2014

Posted by **Sandy** on Sunday, March 16, 2014 at 6:40pm.

y'' - 2y' + y = 0 , y(2) = 0 , y'(2) = 1

- Calculus -
**Steve**, Sunday, March 16, 2014 at 11:33pmy = e^x (c1 + c2*x)

y' = e^x (c1 + c2 + c2*x)

Now plug in the initial conditions to get

e^2 (c1 + 2c2) = 0

e^2 (c1 + c2 + 2c2) = 1

Now just solve for c1 and c2

**Answer this Question**

**Related Questions**

Calculus - Solve the following initial value problem explicitly: y'= ye^-x , y(0...

calculus - How do you solve the initial value problem? (dy/dx)-2y+4=0, y(1)=4

calculus - how do you solve the initial value problem by separation of variables...

calculus - solve the initial value problem by separation of variables dy/dx=-x^...

calculus - solve the initial value problem by separation of variables dy/dx=-xy^...

calculus - solve the initial value problem by separation of variables dy/dx=-xy^...

calculus - solve the initial value problem by separation of variables dy/dx=-x^...

calculus - solve the initial value problem by separation of variables 8. dy/dx=x...

calculus - solve the initial value problem by separation of variables dy/dx=y^(2...

Calculus II - Solve the Initial Value Problem: Let k and Po be positive ...